Remote Ischemic Conditioning Reduced Acute Lung Injury After Traumatic Brain Injury in the Mouse. Issue 2 (February 2021) - Saber, Maha; Rice, Amanda D.; Christie, Immaculate; Roberts, Rebecca G.; Knox, Kenneth S.; Nakaji, Peter; Rowe, Rachel K.; Wang, Ting; Lifshitz, Jonathan
Abstract : ABSTRACT: Traumatic brain injury (TBI) can induce acute lung injury (ALI). The exact pathomechanism of TBI-induced ALI is poorly understood, limiting treatment options. Remote ischemic conditioning (RIC) can mitigate detrimental outcomes following transplants, cardiac arrests, and neurological injuries. In this study, we hypothesized that RIC would reduce TBI-induced ALI by regulating the sphingosine-1-phosphate (S1P)-dependent pathway, a central regulator of endothelial barrier integrity, lymphocyte, and myokine trafficking. Male mice were subjected to either diffuse TBI by midline fluid percussion or control sham injury and randomly assigned among four groups: sham, TBI, sham RIC, or TBI RIC; RIC was performed 1 h prior to TBI. Mice were euthanized at 1-h postinjury or 7 days post-injury (DPI) and lung tissue, bronchoalveolar lavage (BAL) fluid, and blood were collected. Lung tissue was analyzed for histopathology, irisin myokine levels, and S1P receptor levels. BAL fluid and blood were analyzed for cellularity and myokine/S1P levels, respectively. One-hour postinjury, TBI damaged lung alveoli and increased neutrophil infiltration; RIC preserved alveoli. BAL from TBI mice had more neutrophils and higher neutrophil/monocyte ratios compared with sham, where TBI RIC mice showed no injury-induced change. Further, S1P receptor 3 and irisin-associated protein levels were significantly increased in the lungs of TBI mice compared with sham, which was prevented by RIC. However, there was no RIC-associated change in plasma irisin or S1P. At 7 DPI, ALI in TBI mice was largely resolved, with evidence for residual lung pathology. Thus, RIC may be a viable intervention for TBI-induced ALI to preserve lung function and facilitate clinical management. Abstract : Supplemental Digital Content is available in the text